STRATEGI LEARNING START WITH A QUESTION (LSQ) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS KELAS XI MIPA SMAN 3 BUKITTINGGI - Nurva, Mirda Swetherly (journal of RESIDU, 2018)
This research is motivated because not yet achievied the goal of mathematics learning especially students mathematical communication ability. Mathematical communication needs to be the focus of attention in the learning process of mathematics. However, the learning process has not been able to facilitate students to develop mathematical communication ability. One of the learning strategies that can accommodate the aspects in communicating mathematics is Learning Start With A Question (LSQ) strategy. The purpose of this research is to find out whether students mathematical communication ability by applying Learning Start With A Question (LSQ) strategy is better than using conventional learning. This type of research is experimental research. Population in this research is students of class XI MIPA SMAN 3 Teladan Bukittinggi. Sampling is done by simple random sampling technique. The result of this research show that students mathematical communication ability by applying Learning Start With A Question (LSQ) strategy is better than using conventional learning. Keywords : Learning Start With A Question (LSQ), Mathematical Communications Ability